2020
DOI: 10.3390/molecules25040849
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evaluation of the Anticancer Activity of Extracts and Fractions of Lannea barteri Oliv. (Anacardiaceae) on Adherent Human Cancer Cell Lines

Abstract: In western Africa ethnomedicine, Lannea barteri Oliv. (Anacardiaceae) is believed to have activity against gastrointestinal, neurological and endocrine diseases. Previous studies on this plant have revealed antimicrobial, anticholinestrase, anticonvulsant, antioxidant and anti-inflammatory activities. However, the anticancer potential of L. barteri has not been studied to date. The aim of this study was to evaluate the anticancer potential of hot and cold extracts and silica gel column chromatographic fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…48 The stem bark and root of the L. barteri plant contain a variety of phytochemicals, including saponins, coumarins, polyphenols, alkaloids, tannins, quinones, steroids, terpenoids, and flavonoids. 49,50 Saponins, flavonoids, alkaloids, steroids, and glucosides are the main phytochemical components that have been identified in R. communis. The leaves of the plant have been shown to contain significant amounts of phenolic compounds such as gallic acid, quercetin, gentilic acid, rutin, epicatechin, and ellagic acid, as well as monoterpenoids (1, 8-cineole), camphor, and α-sesquiterpenoids (β-caryophyllene).…”
Section: Discussionmentioning
confidence: 99%
“…48 The stem bark and root of the L. barteri plant contain a variety of phytochemicals, including saponins, coumarins, polyphenols, alkaloids, tannins, quinones, steroids, terpenoids, and flavonoids. 49,50 Saponins, flavonoids, alkaloids, steroids, and glucosides are the main phytochemical components that have been identified in R. communis. The leaves of the plant have been shown to contain significant amounts of phenolic compounds such as gallic acid, quercetin, gentilic acid, rutin, epicatechin, and ellagic acid, as well as monoterpenoids (1, 8-cineole), camphor, and α-sesquiterpenoids (β-caryophyllene).…”
Section: Discussionmentioning
confidence: 99%
“…The Anacardiaceae family, especially Lannea species are the site of multiple sources of secondary metabolites such as terpenes, polyphenol [1] [2] [3] [4] alkenyl phenols and alkenyl cyclohexenones [5], steroid [6] [4] and ceramide [7]. Lannea species have numerous pharmacological properties such as antibacterial [4] [5] [8], antoxidant [7] [8] [9], anticancer [10] [11] [12], antihypertensive [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies of some Lannea species have shown their anticancer, antibacterial and antioxidant activities (Sivaraj et al, 2018;Md. Hossain et al, 2018;Sabo et al, 2019;Mbaoji et al, 2020, Ombouma et al, 2022. The edible fruits of most of them are well known for their nutritional value in food or as a food supplement, and have enormous potential contribution in the economy and households (Atato et al, 2011;Sereme et al, 2014;Goudégnon et al, 2016;Diarra et al, 2016;Muhammad et al, 2018;Konaré et al, 2022).…”
Section: Introductionmentioning
confidence: 99%